Deportation of Kalmyks in 1943-1944 over the prism of deported children’s perception - Lidzhieva, Irina V. (The New Research of Tuva, 2014)
Author’s aim was to reflect deportation of Kalmyk people in memories of the children. Article finds its basisin published materials and field notes of author –the interviews and surveys of the people who have been direct witnesses to the violent eviction and special settlements.